Alterations in the Properties of Red Blood Cells in Men with Coronary Artery Diseases after Comprehensive Cardiac Rehabilitation - Krzysztof Gwozdzinski; Anna Pieniazek; Joanna Bernasinska-Slomczewska; Joanna Brzeszczynska; Robert Irzmanski; Anna Jegier (Cardiology Research and Practice)
Purpose. Comprehensive cardiac rehabilitation (CCR) is a complex program aimed at improving the health status of patients with coronary artery disease (CAD), especially those who have been subjected to cardiac interventions (PCI and CABG).The aim of this study was to measure the changes in the properties of red blood cells (RBCs) in men with CAD after cardiac intervention and after participation in CCR program. Methods. In this study, we have investigated the influence of the physical training-based CCR program in 12 men with CAD, after PCI or CABG. The characteristics of RBCs including the basic morphology of RBCs, the conformational state of RBC membrane protein and hemoglobin, acetylcholinesterase activity, membrane fluidity, the osmotic fragility, and thiol concentration in membrane and in hemolysate were measured. Ascorbate concentration and reduced glutathione were also determined. The analysis was performed in men, before and after participation in CCR. The properties of RBCs were observed in connection with the exercise test, and parameters were evaluated before, immediately after, and 1 hour after the exercise test. Results. After CCR, a decrease in the mobility of erythrocyte membrane proteins was observed, which was accompanied by a decrease in lipid fluidity. In addition, immediately after the exercise test and 1 hour later, we measured a decrease in thiol level in hemolysate, but not in the plasma membrane. Unexpectedly, an increase in reduced glutathione concentration one hour after the exercise test after completing comprehensive cardiac rehabilitation was observed. Conclusion. CCR in men with CAD after cardiac intervention is connected with decreased membrane fluidity and decreased membrane protein mobility, which indicates that reduction of oxidative changes in these components occurs.